Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2025)
Table of Content: 1. The role of scientific research in supporting private sector companies to achieve sustainable development "Field study in private sector companies operating in Benghazi" Ms. Fathya G. Shaitir 2. The reality of administrative leadership in Sudanese banks from the employees’ perspective Dr. Khalel Alhamo Alhamdan 3. Good Governance and Its Role in Achieving Sustainable Development Goals in Sudan: An Evaluative Study of Sudan’s Experience Dr. Sayda Mamoun Suliman ,Dr. Hamid Hamad Ibrahim Elfaig 4. The Role of Employment Tests in Selecting Suitable Skills (A field study on administrators in the Government sector for the year 2024 AD) Ms. Hanan Ali Balkhair, Co-Prof. Areej Abdulrahman Alshamasi 5. Role managerial accountant applying for target costing in institution private sectors which higher competition in market KSA: Analytical study Dr. Ezzat Kamal Abdalla Mousa, Dr. Osama Abdelmonge Youssef Akola 6. The Impact of Auditor’s Industrial Specialization on Detecting Financial Statements Fraud for Listed Firm in Saudi Stock Exchange Mr. Tawfeeq Aide Jabal Alsulami , Co-Prof. Mohamed Khamis Zaytoun 7. Perception and Implementation of Integrated Talent Management System (ITMS): A Comparative Study of the Tunisian and Palestinian Public Sectors – Insights from IBM Institute for Business Value Dr. IYAD ABUSAHLOUB, Prof. Chokri ELFIDHA